HUBUNGAN KARAKTERISTIK, GAYA HIDUP, DAN ASUPAN GIZI DENGAN STATUS GIZI PADA LANSIA DI WILAYAH KERJA PUSKESMAS AEK HABIL KOTA SIBOLGA - Adelina Situmorang; Etti Sudaryati; Mhd.Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
The elderly is seen as a group of people who are at risk of experiencing health problems with physical deterioration and often have problems in terms of eating. In fact, although the activity decreases with age, they still require a complete nutrient intake. This study aims to determine the relationship of age, disease status, lifestyle, intake of energy and protein intake and nutritional status of the elderly in Aek Habil Health Center Sibolga. The study was a descriptive survey study with cross-sectional design. The population is elderly aged 55 years and older as 607 people. Determination of the sample using a sample size formula Isgianto (2009) obtained a sample of 83 people. Data collection age, disease status, lifestyle, intake of energy and protein intake using a questionnaire and a food recall form. While the nutritional status data obtained from anthropometric measurements.Univariate test results of research showed that 38.6% of elderly are in the age ≥ 65 years category. 60.2% of elderly disease status was not classified as either. Lifestyle elderly 67.5% classified as not good. Elderly energy intake 92.8% classified as deficit, as well as protein intake was 71.1% classified deficit. Nutritional status of the elderly 60.2% classified as normal. Bivariate test results showed that there was a significant association between illness status of the last 3 months, as well as the lifestyle of protein intake and nutritional status of elderly (p <0.05). While the data age, and energy intake did not show any significant relationship with nutritional status (p> 0.05). It is recommended to the Department of Health Sibolga to create policies to improve nutrition-related counseling of the elderly. Aek Habil Health Center Sibolga in order to provide knowledge and raise awareness about the importance of the elderly run lifestyle, healthy nutrition, to realize a good nutritional status of the elderly, increasing life expectancy, health care and elderly posyandu capable of being upgraded. Keywords: Lifestyle, Nutritional Status, Elderly